Diversidad de la enseñanza universitaria y de la práctica del diseño en México - Morales Holguín, Arodi; González Bello, Edgar Oswaldo (Universidad de Costa Rica, 2021)
University training in the field of design demands the appropriate handling of design methods as a process for creation, a preponderant element for teaching and teachers. In this sense, this text identifies differences in the use of design methods that are used in teaching and professional practice according to the age of the teaching staff. It is a quantitative study supported by the descriptive method and the application, in the period 2018-2019, of a questionnaire to 126 teachers from Mexico of the design areas, differentiated according to their age. The results reveal a diversity marked with age: teachers up to 40 years of age, who possibly received training involving technology and the Internet, conceive of design in a more traditional way, preferring linear-sequential profile methods. From another extreme, those over 40 years of age, who are assumed to have been trained in a technological environment with limitations, showed broader and more progressive perspectives from the complexity promoted by the systemic method. These results also showed statistically significant differences with respect to age. It is concluded that, in reference to teaching and professional practice, the younger teachers, who most likely bet on the technological-digital domain, opted for less updated design methods that privilege the technical aspect, while the subjects with greater age adventure by those of advanced, of a more integral, analytical and critical vision. Assuming this situation contributes to the planning of strategies that guide the improvement of teaching and training in the areas of design.